(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article addresses the issue of abrasive wear, which is the primary cause of machine and mechanism failures, particularly in agricultural equipment. The study focuses on the mechanochemical aspects of wear processes, including the role of physico-chemical interactions between materials and the environment. It has been established that the contact of abrasive particles with metal surfaces creates non-uniform stress, which enhances surface layer activation and increases the intensity of oxidative processes. The article presents the results of a study on the wear resistance of restored component surfaces evaluated across 12 variants. The effectiveness of various materials and welding technologies is examined. It was found that the relative wear resistance of welding using Sv-08G2S wire without modifying additives is 1.0; with nanodiamonds – 0.17, dispersed diamonds – 0.22, and shungite powder – 0.26. The best wear resistance results were achieved using clay and the non-magnetic fraction of detonation mixtures with diamond inclusions on the T-620 electrode. Welding with slip coating did not significantly affect the coefficient of friction. The feasibility of using clays from various deposits was studied, particularly clay from the Pryluky deposit, which reduces surface wear by 27%. In contrast, clay from the Kupyansk deposit increased wear. Conclusions were drawn regarding the optimization of design, technological, and operational measures to ensure the durability of equipment operating in abrasive environments. Recommendations are provided for the selection of materials and surface strengthening methods to improve the maintenance intervals of machinery.